Human impact on tree diametric-species diversity in Scots pine dominated old boreal forest in Fennoscandia - de Quesada, Gonzalo (Helsingin yliopisto, 2019)
Forest structural and compositional diversity is of great importance for forest biodiversity, functioning, and response to disturbances. The purpose of this research was to examine how human impact has affected the structural-compositional diversity of mature pine-dominated boreal forest in boreal Fennoscandia. For this a new approach was used, based on the classification of tree sizes by the diameter at breast height (dbh) and tree species, resulting in a new variable, the diametric-species, the variation of which describes the structural-compositional diversity of the forest. This variable was used to compare the structural-compositional diversity among three forest classes with different degree of human influence (near-natural, selectively logged and managed forest), using rarefaction as the main tool of analysis, complemented by analyses based on common diversity indices. For comparison, the rarefaction analysis was also done for the tree species classification. The results of the rarefaction analysis of the diametric-species showed that the near-natural forest was the most diverse and the managed forest the least diverse. The analysis solely on tree species showed no significant differences among the forest classes of different human impact. The Shannon diversity index showed no significant difference between the forest classes for the diametric-species and only tree species classifications, but the Simpson index found a slight difference between the selectively logged and managed forest classes for the diametric-species classification. Furthermore, the Sorensen index detected a difference among forest classes for diametric-species and failed to detect one for the tree species classification, which supports the rarefaction findings. We conclude that forest management has had a negative impact on forest compositional and structural diversity in mature Scots pine forests. The analysis also shows that the diametric-species classification can be a useful tool for forest diversity analysis and comparison